Peran Penyuluh pada Pengembangan Kelompok Wanita Tani (KWT) di Kecamatan Selupu Rejang - Tria Seftiani; Dodi Aprianto; Gracia Gabrienda (Lembaga Pengembangan Kinerja Dosen, 2024)
Research on the role of extension workers in the development of women's farmer groups (KWT) in Selupu Rejang District, Rejang Lebong Regency aims to analyze the role of extension workers in the development of Women Farmers Groups (KWT) in Selupu Rejang District. The research was conducted in January 2022 in Selupu Rejang District, Rejang Lebong Regency, Bengkulu Province. Determination of the location is done intentionally (purposive sampling) with the consideration that this location is the center of agriculture in the Rejang Lebong highlands which has many farmer groups, one of which is the Women Farmers Group (KWT). This study has two types of primary data that are processed and analyzed, namely quantitative data and qualitative data. Qualitative data from the questionnaires in this study were collected and the answers were studied which then coded the data to obtain quantitative data. The collected data was statistically processed using SPSS for Windows and Microsoft Excel. Checking the completeness and consistency of the answers on the questionnaire sheets, diaries, and audio recordings was carried out at the stage of studying the answers to the questionnaire. The Microsoft Excel program was used at the data coding stage where all quantitative data obtained from the complete and per variable questionnaire answers were entered into the Microsoft Excel program. The stages in analyzing the data are Validity Test, Reliability Test, Likert Scale Analysis and Hypothesis Testing. The role of extension workers is very important in the development of the Women Farmers Group (KWT). Judging from the three categories, namely the role of the instructor as a mentor with a score of 77% in the high category, it can be said to be growing because KWT has been able to innovate by creating new things in farming activities and can also think that farming activities are not only limited to planting but can also perform processing in order to increase the selling value of agricultural products.